DESKRIPSI KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL PADA MATERI SEGI EMPAT - Rahayu, Suci (IKIP Siliwangi, 2021)
Mathematical representation skills are very important for students, because with the ability of representation students can understand a concept or problem and turn it into a concrete form. This study describes the ability of mathematical representation of junior high school students in solving problems in rectangular materials, a question that was given adopted from a government book entitled Mathematics smp grade VII Semester 2 Revised Edition 2017. The research was conducted at SMP Negeri 1 Kotabaru School Year 2020/2021. The study also used descriptive qualitative methods in the next category of student mathematical representation test results on quadrilateral-related questions through a categorization system based on average grades and deviation standards after which they were divided into high, medium and low categories. The results of this article will present students' answers on the question of mathematical representation based on three indicators, namely verbal, image and symbolic representations.